Are men from Mars, women from Venus examining gender differences towards continuous use intention of branded apps - Xin, Jean Lim; Jun, Hwa Cheah; Ng, Siew Imm; Kamal Basha, Norazlyn; Liu, Yide (Elsevier, 2021)
In this age of technology, consumers have become comfortable shopping with their mobile devices. In light of this growing trend, the branded app market has grown steadily, surpassing all other types of mobile commerce. Although many retail businesses go mobile, consumers’ continuous use of the branded app remains a key challenge in gaining a competitive advantage in the contemporary market. By integrating both the stimulus-organism-response (S–O-R) model and gender schema theory (GST), this study aims to investigate how gender differences affect the factors that drive branded app continuous use intention (CUI). Survey data collected from 715 millennial mobile shoppers were analyzed using the partial least squares-structural equation modeling (PLS-SEM) technique. The results demonstrate that telepresence and social presence have a significant effect on customer engagement (CE) and value co-creation (VCC), which consequently impact CUI. Furthermore, the moderation results indicate that both genders play rather different roles in the proposed relations. Therefore, our work contributes to the information system and consumer behavior literature, while providing practitioners with useful information about effective strategies to drive the continuous usage of a branded app.